Ratio Type Estimator for Balanced Sampling Plan excluding Adjacent Units - Tiwari, Neeraj; Banerjie, Jharna; Chandra, Girish; Bhari, Shailja (International Journal of Statistical Sciences, 2024)
The study variables are usually correlated with the auxiliary variables and therefore their correlation could easily be computed. In this paper, the correlation coefficient is used for the estimation procedure, and therefore, we proposed a Horvitz-Thompson ratio-type estimator using correlation coefficient for Balanced Sampling plan excluding Adjacent units (BSA plan). It has been illustrated theoretically and empirically that the proposed Horvitz-Thompson ratio-type estimator is more precise than the Horvitz-Thompson estimator based on BSA plan. The proposed estimator provides an opportunity to utilise the auxiliary information for the estimation of population mean for BSA plan and useful for many real-life experiments. International Journal of Statistical Sciences, Vol.24(1), March, 2024, pp 103-114